Star trek: year five (2019), book 3 ebook - houser, Jody (Star Trek: Year Five (2019), 2021)
Join the crew of the original Starship Enterprise in these all-new adventures as they near the conclusion of their five-year mission. Finally returning to Federation space, the Enterprise and her crew find the Federation isn't quite the same as the one they left behind! Kirk grapples with a very personal Klingon threat, even as the Enterprise begins its homecoming victory tour, and the Federation's upcoming presidential election is upended when Harry Mudd enters the race! All this against the backdrop of a sinister malaise threatening to rot the Federation from within. Terrible secrets are revealed, among them the origin of Gary Seven and the grand designs of the shadowy AEGIS organization. Can Kirk and the Enterprise crew excise this corruption, or will the five-year mission end in failure? Collects issues #13–19 of the series.